Prospective study to the superior virtual education at 2030 - Inche Mitma, Jorge (2012)
This paper analyzes the next problematic question: how to formulate a potential scenario to the virtual superior education at 2030?; for this, will use prospective tools such as structural analyze, actors and objectives matrix (MACTOR) and the SMIC method. This research will allow to the universities adequate their plans and program in order to develop the desired future.